Endoscopic sinus surgery and aspirin desensitization improve otologic-specific SNOT-22 scores - James G. Naples (KeAi Communications Co., Ltd., 2020)
Objective: There are few studies evaluating the impact of Aspirin-exacerbated respiratory disease (AERD) treatment on otologic symptoms. The aim of this study is to evaluate the effects of endoscopic sinus surgery (ESS) and aspirin desensitization (AD) on otologic symptoms in subjects with AERD. Methods: Retrospective chart review of adult patients diagnosed with AERD at our tertiary Care Academic Medical Center - Otorhinolaryngology Department. Charts of adult patients diagnosed with AERD who underwent ESS and ASA desensitization at our institution's AERD Center from 2016 to 2019 were reviewed. Sino-Nasal Outcomes Test 22-item survey (SNOT-22) scores were evaluated for patients at various time points including: pre-surgery, post-surgery/pre-aspirin desensitization, and various times post-desensitization up to >12 months. Within the SNOT-22, otologic-specific subdomain scores were evaluated at similar time points. Patients on immunomodulatory medications other than corticosteroids were excluded from analysis. Results: SNOT-22 scores were analyzed for 121 patients. There was a significant improvement in overall SNOT scores from pre-surgery (44.62) to post surgery/pre-desensitization (23.34) (P < 0.0005). Similarly, SNOT-22 otologic-specific scores also improved after surgery prior to desensitization (3.19–2.04) (P = 0.005). Following AD, the improvement in the overall SNOT-22 continued to improve for up to 12 months (P < 0.005). While the otologic-specific SNOT-22 scores remained stable after surgery and ASA desensitization. Conclusion: ESS and AD reduce otologic-specific SNOT-22 scores and parallel trends in overall SNOT-22 scores. The effect of treatment is durable over the course of 12 months. Future work should aim to correlate otologic SNOT-22 scores with objective otologic data.